KONTRIBUSI KONSILI BUDDHIS KETIGA UNTUK PERKEMBANGAN ABHIDHAMMA THERAVĀDA - Medhācitto, Tri Saputra (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2023)
This research aims to examine the contribution of the third Buddhist council for the development of Theravāda Abhidhamma literature. This research is carried out with library approach by collecting data mainly from canonical texts as well as its commentaries. The recent works written by scholars such as books, journals, and articles are used to elaborate the explanation. Having examined the data collected from the sources, it is known that the third Buddhist councils (saṅgiti/saṅgāyanā) which held during the 3rd century B.C. under the patronage of King Asoka, contributed significant results for the development of Buddhist literature, particularly in the context of Abhidhamma literature. One of the key outcomes of the third Buddhist council was the completion of the Abhidhamma Pitaka, by adding Kathāvatthuppakaraṇa which was composed by Ven. Mogaliputtatissa Thera at the end of the meeting. As result of that, Abhidhamma Pitaka consists of seven books, including Kathāvatthuppakaraṇa. In conclusion, the third Buddhist council marked a crucial point in the development of Theravāda Abhidhamma.